2016
DOI: 10.1038/srep20713
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stable dielectric responses in uniaxially (001)-oriented CaBi4Ti4O15 nanofilms grown on a Ca2Nb3O10− nanosheet seed layer

Abstract: To realize a high-temperature capacitor, uniaxially (001)-oriented CaBi4Ti4O15 films with various film thicknesses were prepared on (100)cSrRuO3/Ca2Nb3O10− nanosheet/glass substrates. As the film thickness decreases to 50 nm, the out-of-plane lattice parameters decrease while the in-plane lattice ones increase due to the in-plane tensile strain. However, the relative dielectric constant (εr) at room temperature exhibits a negligible degradation as the film thickness decreases to 50 nm, suggesting that εr of (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…NS are obtained by an exfoliation process of various layered oxides [31] and transferred by Langmuir-Blodgett (LB) method (Figure 1a,b) [32] on substrates that, when used bare, are non-adapted for complex oxide deposition, such as silicon or glass. The exceptionally rich structural diversity of NS makes them interesting growth templates for oxides [30,[33][34][35][36][37][38][39][40] or metals. [41] SVO has a cubic perovskite structure with a lattice parameter a = 0.384(1) nm [42] whereas CVO is orthorhombically (o) distorted with pseudo-cubic (pc) a pc = a o /√2 = b o /√2 = c o /2 ≈0.377(1) nm.…”
Section: Resultsmentioning
confidence: 99%
“…NS are obtained by an exfoliation process of various layered oxides [31] and transferred by Langmuir-Blodgett (LB) method (Figure 1a,b) [32] on substrates that, when used bare, are non-adapted for complex oxide deposition, such as silicon or glass. The exceptionally rich structural diversity of NS makes them interesting growth templates for oxides [30,[33][34][35][36][37][38][39][40] or metals. [41] SVO has a cubic perovskite structure with a lattice parameter a = 0.384(1) nm [42] whereas CVO is orthorhombically (o) distorted with pseudo-cubic (pc) a pc = a o /√2 = b o /√2 = c o /2 ≈0.377(1) nm.…”
Section: Resultsmentioning
confidence: 99%
“…The NS obtained by exfoliation of layered structures such as Ruddlesden–Popper phases (for instance SrLaTi 2 TaO 10 2– and Ca 2 Ta 2 TiO 10 2– ), Dion–Jacobson phases (for instance (Ca,Sr) 2 (Nb,Ta) 3 O 10 – and LaNb 2 O 7 – ), and Aurivillius phases (for instance (Sr,Bi)­Ta 2 O 7 2– and Bi 4 Ti 3 O 12 2– ) open new perspectives for the integration of oxides onto nonadapted substrates. Among the NS obtained from these layered oxides, Ca 2 Nb 3 O 10 – (CNO) has been used for the growth of various materials as TiO 2 , CaBi 4 Ti 4 O 15 , or (Na 1– x K x )­NbO 3 , SrTiO 3 , and SrRuO 3. , The Dion–Jacobson parent phase KCa 2 Nb 3 O 10 crystallized in the monoclinic system ( a = 0.7741 nm, b = 0.7707 nm, c = 1.4859 nm, β = 97.51°, JCPDS card N°01-075-9853) and is usually described in a larger tetragonal unit cell with lattice constants a = 0.7727 nm and b = 2.9466 nm. , Its structure consists of stacking of slabs of 3 perovskite layers laying in the (001) plane, separated by a cation (K + ) layer.…”
Section: Introductionmentioning
confidence: 99%
“…The common deposition methods to use deposit high quality of the CBTi thin films are rf magnetron sputtering system, Sol-gel process, dip-coating, polymeric precursor method, Metallo-Organic Chemical Vapour Deposition (MOCVD) etc., [7,[15][16][17]. Recently, J.Kimura et al [7] deposited oriented CBTi thin films in rf sputtering system and showed the stability of dielectric constant for high temperatures.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, J.Kimura et al [7] deposited oriented CBTi thin films in rf sputtering system and showed the stability of dielectric constant for high temperatures. PLD is a simple and clean process to get high-quality uniform films.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation